2021
DOI: 10.31729/jnma.7138
|View full text |Cite
|
Sign up to set email alerts
|

Robson’s Group 2 Criteria among Total Caesarean Sections in a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Globally, there is a dramatic rise in cesarean section rate which has increased the maternal morbidity and adverse effects in a subsequent pregnancy. Robson’s classification will aid in the optimization of the cesarean section use, assessment of the strategies aimed to decrease the cesarean section rate and thus improve the clinical practices and quality of care in various health care facilities. The main aim of this study is to find out the prevalence of caesarean section for Robson’s group 2 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…While, several studies have identified Group 5 as the leading contributor to the cesarean section rate, [12][13][14] in this study, it is the second highest contributor. The cause of this high rate in this group is due to our practise of scheduling prelabor cesarean sectionfor all women with a prior cesarean sectionscar without attempting a trial of labor.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…While, several studies have identified Group 5 as the leading contributor to the cesarean section rate, [12][13][14] in this study, it is the second highest contributor. The cause of this high rate in this group is due to our practise of scheduling prelabor cesarean sectionfor all women with a prior cesarean sectionscar without attempting a trial of labor.…”
Section: Discussionmentioning
confidence: 65%
“…The most common indication for cesarean section in this group was fetal distress (34%) and prior cesarean section (33.2%). The high cesarean section rate in this group can be attributed to large number of high risk pregnancy referrals (such as fetal growth restrictions, preeclampsia and other pregnancy or medical complications) 12 that usually required preterm cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at present, cesarean section is felt by professionals and users alike to be commonplace, tending to become, in some countries, the most usual mode of childbirth (Sabatino, 2019). This should be considered deeply as cesarean section increases maternal morbidity and adverse outcomes in a subsequent pregnancy (Gautam et al, 2021).…”
Section: Consequences Of Cesarean Sectionmentioning
confidence: 99%
“…(Dong & Xie, 2021) Robson's classification provides an objective assessment of cesarean section practice (Zamané et al, 2018) Robson's classification is used to optimize the use of cesarean sections, to evaluate strategies to reduce the cesarean section rate, and thus to improve clinical practice and quality of care in different health facilities. (Gautam et al 2021) The Robson classification is becoming a valuable tool for monitoring cesarean sections in countries with low human development indexes. (Tapia et al, 2016) The Robson ten-group classification system is essential for identifying and analyzing contributors to the cesarean section rate.…”
Section: The Importance Of the Robson Classification References Of Sc...mentioning
confidence: 99%
See 1 more Smart Citation